Model-Based Glycaemic Control in Critically Ill Diabetes Mellitus Patients: Monte Carlo Sensitivity Analysis - Razak A.A.; Razak N.N.; Nor Hisham Shah N.; Lee J.W.W.; Abu-Samah A.; Geoffrey Chase J. (Association for Computing Machinery, 2023)
Errors; Glucose; Insulin; Intelligent systems; Intensive care units; Monte Carlo methods; Stars; Stochastic models; Stochastic systems; Critically ills; Diabetes mellitus; Glycemic control; In-silico; In-silico trial; Insulin sensitivity; Intensive care; Malaysians; Model-based OPC; Monte Carlo's simulation; Sensitivity analysis